Implementation of the Small Claims Court in Dispute Case Settlement in Indonesia - Wibowo, Seno Adhi; Wijaya, Massulthan Rafi (Lex Scientia Law Review, 2021)
Dispute settlement through the courts (litigation) is perceived as ineffective and costly. The dispute resolution process through the courts is prolonged and time-consuming due to its very formal and very technical review procedure, high costs of the case, and the likelihood of repeated trials. The number of complaints made against citizens unwilling to deal with the judiciary. The Supreme Court with its authority to address the problems of the courts (litigation), namely by ratifying the 2015 Supreme Court Regulation (Perma) No. 2 concerning the procedures for the settlement of the Small Claims Court, to allow all elements of society to take a new direction of litigation, namely through Small Claims Court a simple, fast and low-cost lawsuit. With this, it hopes that the judicial process in Indonesia will be well underway in the future.